SMOKING HABIT, PHYSICAL ACTIVITY AND HYPERTENSION AMONG MIDDLE AGED MEN[Kebiasaan Merokok, Aktifitas Fisik, dan Hipertensi pada Laki-laki Dewasa] - Rian Diana; Ali Khomsan; Naufal Muharam Nurdin; Faisal Anwar; Hadi Riyadi (Universitas Airlangga, 2018)
Hypertension is a global public health problem. Hypertension prevalence increasing with age, particularly in middle aged men. It is important to identify the modifiable risk factors. The aim of this study was to analyse the correlation of smoking habit, physical activity, and hypertension among middle aged men. This study was conducted in Cianjur District, West Java. 112 men aged 45-59 years old were participated in this cross sectional study. Automatic blood pressure (OMRON Model HEM-7200) was used to measure blood pressure. 24-hour physical activity recall was used to assess physical activity (PA). The correlation between smoking habit and hypertension was analyzed by Chi Square. The correlation between physical activity and hypertension was analyzed by Spearman. This study found that 83.9% subjects had smoking habit. More than half of the subjects (57.2%) had heavy PA. Almost half of the subjects (43.7%) were hypertension. Median of systolic 135.0 mmHg and diastolic 85.0 mmHg. There was a significant correlation between smoking habit (p=0.039) and physical activity (p=0.025) with hypertension. Smoking habit and physical activity correlate with hypertension. Having a moderate to vigorous physical activity regularly particularly in smokers among middle aged men are recommend for decreasing the prevalence of hypertension.